Annual Plan 1994-95 Volume-X X. Education. Sports. Arts & Culture. Hill Areas Government of Assam - Planning Commission (Planning Commission, 1994)
Elementary Education : During the Year 1994-95,An Amount of Rs. 1132.00 Lakhs Has Been Provided Under Elementary Education Out of Which An Amount of Rs. 750.00 Will Be Required For Payment of Salaries of Primary and Middle Schools Teachers. Moreover Rs. 83.00 Lakhs Will Be Required For Provincialization of 40 M.E. Schools and Creation of 300 Costs of L.P. Teachers And the Remaining 299.0 Lakhs Will Be Required For Other Continuing Schemes and Incentive Schemes. Secondary Education : An Amount of Rs.230.00 Lakhs Has Been Provided Under Secondary Education During the Annual Plan 1994-95.
Government of Assam